Origin of internal flow structures in columnar-jointed basalt from Hrepphólar, Iceland: I. Textural and geochemical characterization - Bosshard, Sonja; Mattsson, Hannes; Hetényi, György (2018)
Basalt columns from Hrepphólar (Iceland) show distinct internal structures produced by alternating brighter and darker bands through the column, locally exhibiting viscous fingering features. Here, we present geochemical and petrographic data retrieved from analyses of major and trace elements and mineral chemistry from a cross section of a single basaltic column. This is combined with petrographic descriptions and data on crystal size distributions of plagioclase. We use our data from Hrepphólar to test four existing models that have been proposed to explain banded structures inside columns: (1) deuteric alteration, (2) double-diffusive convection, (3) constitutional supercooling, and (4) crystallization-induced melt migration. We find that the internal structures at Hrepphólar represent primary magmatic features, because approximately 20% of the observed structures crosscut the column-bounding fracture for each meter along the main axis of the column. These features must thus have been formed before the column-delimiting crack advanced. Major and trace element analyses show small but significant variations across the column and strong correlation between oxides like FeO and TiO2, as well as K2O and P2O5. The geochemical variations correlate with the presence of darker/brighter bands visible on a polished surface and can be explained by a variation in the modal proportions of the main phenocryst phases (specifically variable plagioclase and titanomagnetite content). This banding enhances the internal structures apparent in the polished cross section from columnar joints at Hrepphólar. The measured variations in major and trace element geochemistry, as well as mineral chemistry, are too small to distinguish between the proposed band-forming models. Plagioclase crystal size distributions, however, display a systematic change across the column that is consistent with late-stage migration of melt inside the column (i.e., the crystallization induced melt migration hypothesis). The central part of the columns have ...